1999
DOI: 10.1159/000024038
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Th1 and Th2 Immunoregulatory Cytokines by Human Eosinophils

Abstract: Besides cytotoxic mediators, human eosinophils can produce proinflammatory and anti–inflammatory cytokines, as well as growth factors and chemokines. The demonstration that eosinophils from patients could produce IL–5, IL–4 and IL–2 suggested their participation in the regulation of immune response. In the present work, we have examined the presence of Th1 (IFN–γ, IL–2) and Th2 (IL–4, IL–5, IL–10 and IL–13) cytokines in eosinophils from patients or donors by intracellular flow cytometry, and by immunocytochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 7 publications
1
42
0
Order By: Relevance
“…This result suggests that other non-CD4 + non-CD8 + T cells may be the source of this increase (e.g. contamination with granulocytes, detected evenly on day 14 pi by flow cytometry [15,32]). As on day 7 pi, the CD8 + IL10 + population was absent on day 14 pi, whereas the frequency of CD4 + IL10 + cells had increased further.…”
Section: Discussionmentioning
confidence: 92%
“…This result suggests that other non-CD4 + non-CD8 + T cells may be the source of this increase (e.g. contamination with granulocytes, detected evenly on day 14 pi by flow cytometry [15,32]). As on day 7 pi, the CD8 + IL10 + population was absent on day 14 pi, whereas the frequency of CD4 + IL10 + cells had increased further.…”
Section: Discussionmentioning
confidence: 92%
“…Activated eosinophils are one of the primary sources of cytotoxic proteins, proinflammatory cytokines, and growth factors, such as IL‐4, IL‐5, IL‐10, and IL‐13 6, and promote numerous immunoregulatory functions that lead to the progression of inflammation, mucus secretion, tissue remodeling, and angiogenesis 7.…”
mentioning
confidence: 99%
“…E osinophils are important effector cells in allergic diseases, particularly in late-phase reactions, because they release bronchoconstrictor mediators such as leukotriene C 4 and other chemoattractants that cause further influx of inflammatory cells into the tissue (1). Eosinophils produce proinflammatory cytokines and growth factors, including immunoregulatory Th2-type cytokines (2)(3)(4).…”
mentioning
confidence: 99%
“…Eosinophils produce proinflammatory cytokines and growth factors, including immunoregulatory Th2-type cytokines (2)(3)(4). Mucosal damage in asthma is associated with cytotoxic mediators that are released by activated eosinophils, and it has been shown that asthmatic patients who received treatment based on eosinophil counts in sputum had significantly fewer severe asthma exacerbations than patients treated according to standard management therapy (5).…”
mentioning
confidence: 99%